Analisis Pengendalian Persediaan Bahan Baku Dengan Metode EOQ : (Studi Kasus Pada Pabrik Mitra Mandiri Panawangan Ciamis Periode Tahun 2021) - Rully Angie Alwani; Suci Putri Lestari; Depy Muhamad Pauzy (CV. Ulil Albab Corp, 2022)
This study aims to find out how the implementation of raw material inventory control that has been carried out at Mitra Mandiri factories, how to apply the Economic Order Quantity (EOQ) method in controlling raw material inventory at Mitra Mandiri factories. Data collection techniques in this study is to use interview techniques, library research and observation. The method used in this research is descriptive analysis method. The analytical tool used is the method of Economic Order Quantity (EOQ), Safety Stock, ReOrder Point, and Total Inventory Cost. Based on the results of the study, it is known that the calculation of the Economic Order Quantity (EOQ) method shows that the total cost of raw material inventory that must be issued by the company is greater than the total cost of inventory calculated according to the Economic Order Quantity (EOQ) method. Companies should follow the calculation of the Economic Order Quantity (EOQ) method so that they can save on raw material inventory costs, optimize inventory and streamline inventory costs.